The historical symbol in the Umayyad poetry - مهنا, بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aims to study the place as a historical symbol in the poetic text. Especially through the social and political changes in the Umayyad age . That the place doesn't break off its knowledge supply and the accurals of the individual and group memory , as the poetic text in this as one of its ingredients and reference marks containing those cultural contents and dimensions which take part in building its marker .